Intravenous Bone Marrow Mononuclear Cells Transplantation in Aged Mice Increases Transcription of Glucose Transporter 1 and Na+/K+-ATPase at Hippocampus Followed by Restored Neurological Functions - Takeuchi, Yukiko; Okinaka, Yuka; Ogawa, Yuko; Kikuchi-Taura, Akie; Kataoka, Yosky; Gul, Sheraz; Claussen, Carsten; Boltze, Johannes; Taguchi, Akihiko (Frontiers in Aging Neuroscience, 2020)
We recently reported that intravenous bone marrow mononuclear cell (BM-MNC) transplantation in stroke improves neurological function through improvement of cerebral metabolism. Cerebral metabolism is known to diminish with aging and the reduction of metabolism is one of the presumed causes of neurological decline in the elderly. We now report herein that transcription of glucose transporters, monocarboxylate transporters and Na+/K+-ATPase are down-regulated in the hippocampus of aged mice with impaired neurological functions. Intravenous BM-MNC transplantation in aged mice stimulated the transcription of glucose transporter 1 and Na+/K+-ATPase α1 followed by restoration of neurological function. As glucose transporters and Na+/K+-ATPases are closely related to cerebral metabolism and neuronal function, our data indicate that BM-MNC transplantation in aged mice has the potential to restore neuronal function through activating transcription of glucose transporter and Na+/K+-ATPase. Furthermore, our data indicate that changes in transcription of glucose transporter and Na+/K+-ATPase could be surrogate biomarkers for age related neuronal impairment as well quantifying the efficacy of therapies.